Strong circularly polarized luminescence of mixed lanthanide coordination polymers with control of 4f electronic structures. Issue 16 (15th April 2021) - Islam, Md Jahidul; Kitagawa, Yuichi; Tsurui, Makoto; Hasegawa, Yasuchika
Abstract : This paper reports chiral mixed Eu(iii )–Ln(iii ) coordination polymers (Ln = Gd and Sm) for the enhancement of the emission quantum yield ( Φ tot ≥ 50%), achieved via control of 4f electronic structures. Abstract : This paper reports chiral mixed Eu(iii )–Ln(iii ) coordination polymers (Ln = Gd and Sm) with a high dissymmetry factor of circularly polarized luminescence ( g CPL = 0.15) for the enhancement of the emission quantum yield ( Φ tot ≥ 50%), achieved via control of 4f electronic structures.